Mindful consumption of second-hand clothing: the role of eWOM, attitude and consumer engagement - Mohammad, Jihad (Emerald Group Holdings Ltd., 2021)
Purpose: This study aims to examine the direct and indirect effects of electronic word of mouth (eWOM) on mindful consumption behaviour (MCB) in a sustainable clothing purchase context. In addition, it examines the mediating effect of “consumer engagement” and “attitude towards second-hand clothes”. Design/methodology/approach: The data were gathered through a self-administered questionnaire survey from Malaysian consumers who had experience in purchasing second-hand clothes. A total of 175 complete and useable questionnaires were obtained, which were then analysed by using the structural equation modelling-partial least square (SEM-PLS) technique. Findings: The results of this study indicate support for the direct effect of eWOM on consumers' attitude towards second-hand clothes, consumer engagement and consumers’ MCB. The results also supported the relationship between consumer engagement and MCB, but the link between attitude and mindful consumption (MC) was not supported. Furthermore, the study confirmed the mediating effect of consumer engagement between eWOM and consumers’ MCB but did not support the mediating effect of attitude towards second-hand clothes. Originality/value: This study is amongst the pioneers to elucidate MCB in the context of sustainable clothing. It examines the direct and indirect effects of eWOM on MCB, which has not been tested in the past literature. The mediating effects of consumer engagement and attitude towards second-hand clothes on the relationship between eWOM and MCB are also comparatively new links.